Effect of pressure on electronic and optical properties of magnesium silicide and germanide - Shaposhnikov, Victor L.; Krivosheeva, Anna V.; Borisenko, Victor E. (Journal of the Belarusian State University. Physics, 2017)
A detailed theoretical study of electronic and optical properties of magnesium silicide Mg2Si and germanide Mg2Ge under hydrostatic and uniaxial pressure has been performed by means of linearized augmented plane wave method. It has been found that the direct gap at the G-point increases linearly with the rise of the pressure, while the indirect one decreases becoming zero under the hydrostatic pressure of about 10 GPa. The decrease of the static dielectric constant with the rise of the pressure reflects the changes in the direct gap. Quite different results were observed for uniaxial deformation of the lattice. Either compression or tension of the lattice strongly decreases the indirect band gap. The direct gap depends linearly on the both types of deformations, but dependencies have different slopes.